Body fatness at an early age and risk of colorectal cancer. Issue 4 (26th October 2017) - Hidayat, Khemayanto; Yang, Chun‐Mei; Shi, Bi‐Min
Abstract : While there is convincing evidence that excess body fatness in adulthood is positively associated with colorectal cancer risk, the association between body fatness at an early age (≤30 years) and the risk of colorectal cancer has been equivocal. The present meta‐analysis was performed to clarify this association. PubMed and Web of Science databases were searched for relevant studies that investigated this association. The risk estimates from each study were transformed into a continuous variable for each 5 kg/m 2 increase in body mass index (BMI). A random effects model was used to calculate the summary relative risks (RRs) with 95% confidence intervals (CIs). A total of 15 observational studies (13 cohort studies and two case‐control studies) were included in this meta‐analysis. Each 5 kg/m 2 increase in BMI was significantly associated with a 13% (RR 1.13, 95% CI 1.08, 1.19), 17% (RR 1.17, 95% CI 1.09, 1.25) and 8% (RR 1.08, 95% CI 1.04, 1.11) higher risk of colorectal cancer overall, in men, and in women, respectively. Substantial heterogeneity was observed across studies. Based on the anatomic subsite, each 5 kg/m 2 increase in BMI was significantly associated with a 14% (RR 1.14, 95% CI 1.07, 1.22) higher risk of colon cancer, whereas no association (RR 1.03, 95% CI 0.95, 1.13) was observed with rectal cancer. In summary, body fatness at an early age may affect colon cancer risk later in life. Prevention of overweight and obesity in young individuals should be emphasized to prevent early‐onset colon cancer attributed to excess body fatness. Abstract : What's new? Obesity is associated with an increased risk of colorectal cancer. But does being overweight early in life affect later risk? In this meta‐analysis, the authors found that people with a higher body mass index (BMI) before the age of 30 had an increased risk of colon cancer (but not rectal cancer) later in life. Working with overweight and obese young people to help them achieve a lower BMI may thus provide a useful preventive strategy to reduce the risk of earlier‐onset colon cancer.